EFFECTS OF CHEMICAL PEELING WITH ACID COMPLEX ON MELASMA: A CASE ANALYSIS - Žuromskienė, Eglė; Gintvainytė, Julita (Slauga. Mokslas ir praktika, 2023)
Melasma is a chronic disorder of skin melanogenesis, manifested by irregularly shaped pigment spots. Although most pigmentation disorders are benign or non-specific, some skin pigmentation disorders can cause cosmetic or psychological problems. Regardless of which melasma reduction method is chosen, the use of sunscreen is mandatory, not only during prescribed treatments or using home remedies, but also after completing all stages of treatment. Chemical peels are considered one of the most effective cosmetic facial procedures to reduce melasma, but peels can also have additional effects on the skin: moisturizing, anti-inflammatory, antioxidant, wrinkle-correcting effects. This is one of the reasons why beauticians choose chemical peels not only to reduce melasma, but also to affect other skin aesthetic problems. Although there is a large selection of chemical peels on the cosmetic market to solve the same problem, alpha-hydroxy acids such as glycolic, mandelic or kojic acid are a common choice among professionals. The purpose of the research is to determine the effect of chemical peels with an acid complex on melasma, using such research methods as literature analysis, oral survey, comparative analysis and observation. After completing a course of 4 chemical peels with an acid complex, the result is positive. The areas affected by melasma became lighter, the surface moisture level of the skin increased.